Application of Photodynamic Therapy in Pediatric Dentistry: Literature Review - Tamiris Silva; Ana Júlia Lacerda Lunardi; Ana Carolina Santos Menezes Barros; Amanda Rafaelly Honório Mandetta; Elizabeth Grudzien; Magdalena San-Martín; Anna Carolina Ratto Tempestine Horliana; Sandra Kalil Bussadori; Lara Jansiski Motta (MDPI AG, 2023)
Microbiological control of dental pathologies presents a significant clinical challenge for dental surgeons, particularly considering drug-resistant microorganisms. To address this issue, Antimicrobial Photodynamic Therapy (PDT) has emerged as an effective and complementary technique for microbial reduction. This therapy involves the application of a photosensitizer dye (PS) either topically or systemically, followed by exposure to low-power lasers with appropriate visible light wavelengths. PDT has found a valuable place in dentistry across various specialties, including surgery, periodontics, endodontics, dentistry, implantology, orthodontics, and pediatrics. In the realm of pediatric dentistry, managing microorganisms during dental treatments has become a major challenge. Considering its promising results and ease of application, Photodynamic Therapy presents an interesting alternative for clinical practice. However, it is important to note that specific protocols must be followed for each application, encompassing the type of photosensitizer, concentration, pre-irradiation time, light type, wavelength, energy, power, and mode of light delivery. Researchers have been steadily refining these protocols to facilitate PDT's integration into clinical practice. The objective of this review is to describe in which procedures and oral health problems in children PDT can be applied. In this sense, we list what the literature brings about the possibilities of applying PDT in a pediatric dentistry clinic.